Pleasant Events, Hopelessness, and Quality of Life in Rural Older Adults. Issue 1 (17th July 2015) - Scogin, Forrest; Morthland, Martin; DiNapoli, Elizabeth A.; LaRocca, Michael; Chaplin, William
Abstract: Purpose: Rural older adults are susceptible to depression and reduced quality of life. This study explored contrasting explanations (behavioral vs cognitive route) for the relation of emotional distress with quality of life. Methods: This retrospective study included rural older adults (N = 134) with reduced quality of life and increased psychological symptoms. Multiple mediation analysis was conducted to test the indirect effect of engagement in pleasant events and hopelessness on the emotional distress and quality of life relation. Findings: Both engagement in pleasant events and hopelessness were found to partially mediate the relation between emotional distress and quality of life. Conclusions: Targeting both hopelessness and engagement in pleasant events may be helpful in improving the quality of life of vulnerable, rural older adults.